100 decisive battles : from ancient times to the present - Davis, Paul K. 1952- (Santa Barbara, Calif. : ABC-CLIO, 1999)
Surveys the one hundred most decisive battles in world history from the Battle of Megiddo in 1469 B.C. to Desert Storm, 1991.
Includes bibliographical references (p. 441-451) and index.
Keywords: Battles; Military history; Battles; Military history